ChemInform Abstract: Highly Selective Allylborations of Aldehydes Using α, α‐Disubstituted Allylic Pinacol Boronic Esters. Issue 49 (9th December 2014) - Hesse, Matthew J.; Essafi, Stephanie; Watson, Charlotte G.; Harvey, Jeremy N.; Hirst, David; Willis, Christine L.; Aggarwal, Varinder K.
Abstract Tetrasubstituted homoallylic alcohols with exceptional levels of diastereo‐and enantioselectivity are synthesized through allylboration of aldehydes.